2021
DOI: 10.1155/2021/5560596
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bacterial Load and Antibiotic Resistance Pattern of Staphylococcus aureus from Ready-to-Eat Raw Beef in Bahir Dar City, Ethiopia

Abstract: Background. Staphylococcus aureus is one of the most important causes of food-borne intoxication and the most frequent antibiotic-resistant pathogen in the world. Regular evaluation of the current safety status of food is a proactive measure to minimize the possible danger of food-borne pathogens. Therefore, this study was conducted to assess the bacterial load and antibiotic resistance profile of S. aureus from ready-to-eat raw beef in Bahir Dar city, Ethiopia. Methodology. This cross-sectional study was cond… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
(35 reference statements)
2
3
0
Order By: Relevance
“…High S. aureus antibiotic resistance was observed for penicillin (93.06%) followed by amoxicillin and erythromycin and our results are comparable to that reported by Tsehayneh et al [60]. Forty-five (62.5%) S. aureus isolates in this study showed multidrug resistance and this was lower than 98% (54 out of 55 S. aureus isolates) recently reported by Tsehayneh et al [60].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…High S. aureus antibiotic resistance was observed for penicillin (93.06%) followed by amoxicillin and erythromycin and our results are comparable to that reported by Tsehayneh et al [60]. Forty-five (62.5%) S. aureus isolates in this study showed multidrug resistance and this was lower than 98% (54 out of 55 S. aureus isolates) recently reported by Tsehayneh et al [60].…”
Section: Discussionsupporting
confidence: 87%
“…This high sensitivity of the S. aureus isolates has great therapeutic relevance because these antibiotics can be used to treat infections caused by this bacterium in our resource poor community. High S. aureus antibiotic resistance was observed for penicillin (93.06%) followed by amoxicillin and erythromycin and our results are comparable to that reported by Tsehayneh et al [60]. Forty-five (62.5%) S. aureus isolates in this study showed multidrug resistance and this was lower than 98% (54 out of 55 S. aureus isolates) recently reported by Tsehayneh et al [60].…”
Section: Discussionsupporting
confidence: 87%
“…57 % of the food samples had total aerobic plate count in the range of 2.67–8.89 log cfu/g of sample. S. aureus was present in almost half of 66 food samples analyzed ranging from 2.45 to 8.65 log cfu/g of sample which exceeds the satisfactory limits of 4 log cfu/g [ 36 ]. The presence of S. aureus above the satisfactory limit is a clear indication of the poor personal hygiene of the person handling the food [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, S. aureus was determined between 16% and 54.4% of the raw beef samples [ 23 – 27 ]. For instance in a study in Iran by Zeinab Torki, S. aureus was found in 16% of raw beef for retail sale, [ 23 ] in a study by Bizuneh Tsehaynah, 54.5%, [ 24 ] and in a study by Qianting Ou, and 29.2% [ 25 ]. In a study conducted in Japan, it was also reported that 32.8% of the raw beef samples were contaminated by S.aureus [ 26 ].…”
Section: Discussionmentioning
confidence: 99%